The Relationship of corporate governance and earnings management as witnessed in the various listed companies in the Philippines - Dilangalen, Nur Halifa N. (Animo Repository, 2010)
The paper focused on understanding how corporate governance and earnings management are related with each other. Samples were obtained from a population of publicly listed companies in the Philippines in order to do this. The study was made possible by analyzing the annual reports from years 2008-2009 to identify the variables needed in measuring corporate governance and earnings management. Earnings management (EM), on the other hand, was measured by computing for abnormal accruals using the Modified Cross Sectional Jones model. The relationship between corporate governance (CG) and EM was tested using the Pearson Correlation and regression analysis with the aid of Stata 10 Software. After conducting a number of tests, the Random Effect GLS regression model was used in the study. The results show that not all CG variables are significant which may be due to the limitations stated in the paper. In addition to this, Hutchinson and Gul (2004) propose that some variables may not be appropriate for all firms. There is a significant relationship between CG and EM only in terms of board size, audit committee independence and product market competition.